1980
DOI: 10.1111/j.1530-0277.1980.tb04838.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute Ethanol Administration Causes Transient Impairment of Blue‐Yellow Color Vision

Abstract: The higher incidence of blue-yellow color blindness (tritanopia) found among alcoholics could be due to genetic or acquired factors. The acute administration of ethanol to alcoholics and normal subjects transiently resulted in poorer color discrimination in all spectra but with significantly more errors in the blue-yellow versus the red-green color range (p < 0.005, p < 0.01). Thus, ethanol appears to act as a toxin to inner retinal layers, which could account for the higher incidence of tritanopia found among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

1986
1986
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 13 publications
0
11
1
Order By: Relevance
“…However, Verriest et al [42] and Russell et al [34] established that color vision loss was associated with alcoholism, and Urban and LukasÏ [39] found that the mean P1 wave latency in evoked potentials was prolonged in workers exposed to toluene. Such changes could be interpreted as a subclinical sign of dysfunction of the central nervous system related to exposure to toluene and alcohol consumption.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, Verriest et al [42] and Russell et al [34] established that color vision loss was associated with alcoholism, and Urban and LukasÏ [39] found that the mean P1 wave latency in evoked potentials was prolonged in workers exposed to toluene. Such changes could be interpreted as a subclinical sign of dysfunction of the central nervous system related to exposure to toluene and alcohol consumption.…”
Section: Discussionmentioning
confidence: 97%
“…Color vision impairment has been reported to be dependent on age and on [4,13,20,32,33] and on alcohol consumption [34]. It can be monocular or localized unequally in the eyes [9], classi®ed in the yellow-blue or red-green range loss [42].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, age and alcohol play a signi®cant role, which has often been referred to in the literature [5,10,11,14,21,27].…”
Section: Discussionmentioning
confidence: 99%
“…However, there are some studies on organic solvents that make a temporal assignment possible. Ethanol has been shown to cause acute dyschromatopsia of the blue-yellow type after ingestion (Russel et al 1980;Zrenner et al 1986). The color vision impairment of 20 workers exposed to styrene did not improve after a holiday of 1 month (Gobba et al 1991).…”
Section: Toxicity Of Solvents To the Visual Systemmentioning
confidence: 98%